Darītāja un izjutēja lomas robežošanās latviešu valodā - Vogina, Līga (Baltistica, 2012)
BOUNDARIES OF AGENT AND EXPERIENCER IN LATVIANSummaryThe deep sentence structure is reflected in the surface sentence structure. There is no doubt that the actor is an important participant in the semantics of the sentence, and the patient is important in the transitive verb argument structure. Other participant roles form periphery of the situation.The article deals with the issue of boundaries between agent and experiencer roles. In Latvian, both agent and experiencer employ the same means of expression – both participants syntactically can be expressed by the subject. The aim of this article is to clarify whether it is easy to divide these participant roles and what criteria help to make a more objective division. The identification of prototypical roles helps to divide agent and experiencer. The more typical agent features the participant has, the more typical agent the participant is. The comparison of two Latvian examples Meitenes skrien (Girls run) and Laiks tiešām skrien (Time really runs) demonstrates that the prototypical agent is meitenes (girls). The noun laiks (time) is a less typical agent because the predicate run in this sentence is used figuratively.The prototypical agent is an animate controller of the situation who willingly performs an action with a clear purpose and uses his energy to be able to realize the action. The non-typical agent is an inanimate thing or natural phenomenon that can evoke an action or reach a definite state. The prototypical experiencer is an animate participant (human being or animal) who is able to feel, to comprehend information but is not a controller of the situation. The non-typical experiencer can be an inanimate thing or plant. Figuratively speaking, the experiencer is the witness of the situation, while the agent is the author of the situation.
Keywords: Latvian; syntax; agent; eksperiencer; syntactic roles